2020
DOI: 10.1111/jfpe.13596
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymeric films based on whey protein isolate/lignin microparticles for waste recovery

Abstract: Lignin is a source of phenolic compounds. It can be an excellent raw material for the production of films with whey protein isolate (WPI). The present study investigates WPI films with lignin microparticles (LMP). The structural, morphological, physical (thermal and mechanical analysis, water vapor barrier, color parameters, and transparency) properties, and the antioxidant properties were determined. The concentration of LMP were 0, 0.25, 0.50, and 0.75% (w/w). Structural analysis showed the addition of LMP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The LMP was produced according to Gomide et al, 6 and the films were produced by the casting technique according to Azevedo et al 22 WPI and glycerol were used at 6% (w/v) in relation to the volume of solution and 30% (w/w) in relation to the base polymer. For the production of the control film (CF), WPI and glycerol were dissolved separately in distilled water under stirring for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LMP was produced according to Gomide et al, 6 and the films were produced by the casting technique according to Azevedo et al 22 WPI and glycerol were used at 6% (w/v) in relation to the volume of solution and 30% (w/w) in relation to the base polymer. For the production of the control film (CF), WPI and glycerol were dissolved separately in distilled water under stirring for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Its chemical structure has types and numbers of bonds that vary according to the source and extraction methods. The advantages of lignin as an antioxidant agent include its attractiveness as a natural and biodegradable source obtained as a co‐product in the pulp and paper industry, low cost and good availability 6,13–18 . A previous study on the development of WPI‐based films and lignin microparticles (LMPs) showed a good dispersion of LMP (0.25 and 0.50 w/w) in the WPI polymeric matrix, with improved thermal stability, resistance to stiffness and enhanced water vapour barrier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained data by the study of Sukatta et al (19) revealed that film imparts remarkable antioxidant activity (even better than BHT and α-tocopherol) and mediocre antibacterial effects toward S. aureus. Moreover, the results of the addition of paprika extract and coconut EO (20), microparticles of lignin (29), and α-tocopherol (30) to WP-based films are outlined in Table 1.…”
Section: Whey Protein-based Films With Antioxidant Activitymentioning
confidence: 99%
“…This waste volume has been improperly disposed of for many years and has generated enormous environmental problems. Currently, the food industry has developed alternatives to minimize whey disposal, including use in food products such as dairy drinks, ice cream, and WPI production (Carvalho et al, 2019;Carvalho et al, 2020;de Oliveira, Ugucioni, da Rocha, & Borges, 2019;Galus & Kadzi nska, 2019;Gomide et al, 2021). WPI films stand out for their advantages, such as a high oxygen barrier and a good film-forming capability.…”
Section: Introductionmentioning
confidence: 99%